Immune Responses to Influenza Virus and Its Correlation to Age and Inherited Factors - Bahadoran, Azadeh; Lee, Sau H.; Wang, Seok M.; Manikam, Rishya; Rajarajeswaran, Jayakumar; Raju, Chandramathi S.; Sekaran, Shamala D. (Frontiers in Microbiology, 2016)
Influenza viruses belong to the family Orthomyxoviridae of enveloped viruses and are an important cause of respiratory infections worldwide. The influenza virus is able to infect a wide variety species as diverse as poultry, marine, pigs, horses and humans. Upon infection with influenza virus the innate immunity plays a critical role in efficient and rapid control of viral infections as well as in adaptive immunity initiation. The humoral immune system produces antibodies against different influenza antigens, of which the HA-specific antibody is the most important for neutralization of the virus and thus prevention of illness. Cell mediated immunity including CD4+ helper T cells and CD8+ cytotoxic T cells are the other arms of adaptive immunity induced upon influenza virus infection. The complex inherited factors and age related changes are associated with the host immune responses. Here, we review the different components of immune responses against influenza virus. Additionally, the correlation of the immune response to age and inherited factors has been discussed. These determinations lead to a better understanding of the limitations of immune responses for developing improved vaccines to control influenza virus infection.